Otoferlin as a multirole Ca2+ signaling protein: from inner ear synapses to cancer pathways - Jean-Christophe Leclère; Jean-Christophe Leclère; Didier Dulon; Didier Dulon (Frontiers in Cellular Neuroscience, 2023)
Humans have six members of the ferlin protein family: dysferlin, myoferlin, otoferlin, fer1L4, fer1L5, and fer1L6. These proteins share common features such as multiple Ca2+-binding C2 domains, FerA domains, and membrane anchoring through their single C-terminal transmembrane domain, and are believed to play a key role in calcium-triggered membrane fusion and vesicle trafficking. Otoferlin plays a crucial role in hearing and vestibular function. In this review, we will discuss how we see otoferlin working as a Ca2+-dependent mechanical sensor regulating synaptic vesicle fusion at the hair cell ribbon synapses. Although otoferlin is also present in the central nervous system, particularly in the cortex and amygdala, its role in brain tissues remains unknown. Mutations in the OTOF gene cause one of the most frequent genetic forms of congenital deafness, DFNB9. These mutations produce severe to profound hearing loss due to a defect in synaptic excitatory glutamatergic transmission between the inner hair cells and the nerve fibers of the auditory nerve. Gene therapy protocols that allow normal rescue expression of otoferlin in hair cells have just started and are currently in pre-clinical phase. In parallel, studies have linked ferlins to cancer through their effect on cell signaling and development, allowing tumors to form and cancer cells to adapt to a hostile environment. Modulation by mechanical forces and Ca2+ signaling are key determinants of the metastatic process. Although ferlins importance in cancer has not been extensively studied, data show that otoferlin expression is significantly associated with survival in specific cancer types, including clear cell and papillary cell renal carcinoma, and urothelial bladder cancer. These findings indicate a role for otoferlin in the carcinogenesis of these tumors, which requires further investigation to confirm and understand its exact role, particularly as it varies by tumor site. Targeting this protein may lead to new cancer therapies.